The Dynamics of Reading Habits in English Education Students: A Sociological Analysis - Agatha, Maybelline; Kuspiyah, Hastuti Retno; Muklas, M. (JLE: Journal of Literate of English Education Study Program, 2025)
This study explores the reading habits of fourth-semester students in the English Education Program at Nurul Huda University through a sociological perspective. It aims to describe students’ reading behaviors and examine the influence of social factors such as peer dynamics, family support, and digital media exposure. Descriptive method is used for this study, data were collected through classroom observation and a bilingual Likert-scale questionnaire. The findings indicate that although students acknowledge the value of reading, their practices are often inconsistent, hindered by academic workload, the pervasive influence of social media, and a limited reading culture in their immediate environment. A strong preference for visual and digital content over academic texts was also observed, raising concerns about the development of critical reading skills. The study concludes that reading habits are not solely driven by individual motivation but are significantly shaped by sociocultural contexts. Therefore, educational institutions should cultivate a literacy-friendly environment that addresses these social dimensions to support the development of effective and sustained reading practices, particularly for future educators.